2000
DOI: 10.1177/106342660000800105
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnic Differences in ADHD as Assessed by Behavior Ratings

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common childhood disorder. Research suggests that ADHD is 4 to 9 times more frequent in males than females, and the possibility of underidentification in females and overidentification in males has been suggested as an explanation for these statistics. As part of the diagnostic process, teachers are frequently asked to complete behavior rating scales. There is a lack of empirical data concerning the extent to which gender differences are evident on such rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 40 publications
(43 reference statements)
7
35
0
1
Order By: Relevance
“…The girls who met criteria for ADHD exhibited higher levels of conduct, mood, and anxiety problems, received lower ratings of global functioning, and had more school problems than the comparison girls. In addition, a large population-based study by Reid et al (2000) found that boys with ADHD are rated by teachers as exhibiting more conduct problems than girls with ADHD.…”
mentioning
confidence: 99%
“…The girls who met criteria for ADHD exhibited higher levels of conduct, mood, and anxiety problems, received lower ratings of global functioning, and had more school problems than the comparison girls. In addition, a large population-based study by Reid et al (2000) found that boys with ADHD are rated by teachers as exhibiting more conduct problems than girls with ADHD.…”
mentioning
confidence: 99%
“…Many researchers have shown that externalizing behaviors commonly co-occur, as demonstrated in the current study (Abikoff, et al, 1993;Goldstein, 1996;Kashani, et al, 1979;Reid, et al, 2000;Schachar, et al, 1986;Stevens, et al, 1998). Higher ratings of hyperactivity in the home environment were predictive of all three externalizing behaviors as rated by parents, including measures of aggression, hyperactivity, and conduct problems, but only teacher ratings of hyperactivity.…”
Section: Externalizing Behaviorssupporting
confidence: 64%
“…Furthermore, the BASC scales were developed such that each item contributes to only one scale, thus preserving the distinctiveness of the construct (Reynolds & Kamphaus, 1992). Reid, et al (2000) advocate for the use of separate norms males and females to assess AD/HD symptomatology with behavior rating scales. In contrast, Silverthorn and colleagues (1996) concluded that separate norms by gender were not warranted based on their finding that girls and boys with AD/HD did not differ on measures of severity and that diagnostic cut-scores identified boys and girls with equivalent levels of impairment.…”
Section: Basementioning
confidence: 99%
See 1 more Smart Citation
“…La confirmación de la cuarta hipótesis de la investigación, esto es, que los niños manifiestan más problemas exteriorizados que las niñas, es congruente con los hallazgos obtenidos por otros estudios tanto en población infantil como adolescente (Crijnen et al, 1997;Reid et al, 2000;Rescorla et al, 2007). A pesar de que las diferencias de género en exteriorización de problemas es más consistente, algunos estudios señalan que las diferencias entre ambos sexos pueden diferir según el tipo de conducta evaluada y la edad del sujeto.…”
Section: Discussionunclassified